A component-based reverse engineering approach: decomposing web pages to facilitate maintenance and reusability - Thiam, K.C.; Renaud, K.V. (2009)

(untitled)
Web page creation has become even easier with the emergence of many different authoring tools. Unfortunately, these authoring tools do not guarantee that the design is effective or that the resulting web pages are usable and perform well. With more Web pages being designed and implemented by novices, Web page maintenance has become more difficult. Furthermore, pressure to deploy Web applications within a short time has led to pages being published without first undergoing thorough testing. Consequently, such pages are more likely to be modified and refined frequently after deployment. Moreover, the heterogeneous operational platform and environment of Web-based applications, as well as diversified user base of the applications, inevitably poses unpredicted new requirements after deployment. Therefore, the maintenance of Web pages needs to be carried out more frequently and rapidly as compared to traditional software maintenance. This research proposes a reverse engineering framework that can be used to facilitate and ease maintenance of Web pages. Existing Web pages are decomposed into different types of components to facilitate systematic examination. A proof-of-concept prototype tool was developed to assess the feasibility of the proposal. Initial evaluation has delivered encouraging results.